Internet-Delivered Interventions for Depression and Anxiety Symptoms in Children and Young People: A Systematic Review and Meta-analysis. - Richards, Derek; Eilert, Nora (My University, 2022)
Background: Mental health difficulties in children and adolescents are highly prevalent; however, only a minority receive adequate mental health care. Internet-delivered interventions offer a promising opportunity to increase access to mental health treatment. Research has demonstrated their effectiveness as a treatment for depression and anxiety in adults. This work provides an up-to-date examination of the available intervention options and their effectiveness for children and young people (CYP). Objective: In this systematic review and meta-analysis, we aimed to determine the evidence available for the effectiveness of internet-delivered interventions for treating anxiety and depression in CYP. Methods: Systematic literature searches were conducted throughout November 2020 using PubMed, PsycINFO, and EBSCO academic search complete electronic databases to find outcome trials of internet-delivered interventions treating symptoms of anxiety and/or depression in CYP by being either directly delivered to the CYP or delivered via their parents. Studies were eligible for meta-analysis if they were randomized controlled trials. Risk of bias and publication biases were evaluated, and Hedges g between group effect sizes evaluating intervention effects after treatment were calculated. Meta-analyses used random-effects models as per protocol. Results: A total of 23 studies met the eligibility criteria for the systematic review, of which 16 were included in the meta-analyses, including 977 participants in internet-delivered treatment conditions and 1008 participants in control conditions across 21 comparisons. Random-effects models detected a significant small effect for anxiety symptoms (across 20 comparisons; Hedges g=-0.25, 95% CI -0.38 to -0.12; P<.001) and a small but not significant effect for depression (across 13 comparisons; Hedges g=-0.27, 95% CI -0.55 to 0.01; P=.06) in favor of internet-delivered interventions compared with control groups. Regarding secondary outcomes, there was a small effect of treatment across 9 comparisons for impaired functioning (Hedges g=0.52, 95% CI 0.24-0.80; P<.001), and 5 comparisons of quality of life showed no effect (Hedges g=-0.01, 95% CI -0.23 to 0.21; P=.94). Conclusions: The results show that the potential of internet-delivered interventions for young people with symptoms of anxiety or depression has not been tapped into to date. This review highlights an opportunity for the development of population-specific interventions and their research to expand our current knowledge and build an empirical base for digital interventions for CYP.
PUBLISHED
Keywords: Internet-delivered interventions; Children and young people; Depression; Anxiety; Digital health